MPLS VPN security - Behringer, Michael H. (Cisco ; Pearson Education [distributor], 2005)
This is the eBook version of the printed book. A practical guide to hardening MPLS networks Define ""zones of trust"" for your MPLS VPN environment Understand fundamental security principles and how MPLS VPNs work Build an MPLS VPN threat model that defines attack points, such as VPN separation, VPN spoofing, DoS against the network's backbone, misconfigurations, sniffing, and inside attack forms Identify VPN security requirements, including robustness against attacks, hiding of the core infrastructure, protection against spoofing, and ATM/Frame Relay security comparisons Interpret com.